(untitled) (Applied Biological Research, 2018)
The present study was conducted on gall bladder of < 1 year-old sheep (n = 9) to elucidate the distribution of enzymes viz., alcoholic dehydro genase, glucose-6-phosphate dehydrogenase, glutamic dehydrogenase, lactic dehydrogenase, malic dehydrogenase, reduced nicotinamide adenine dinucleotide diaphorase, reduced nicotinamide adenine dinucleotide phosphate-diaphorase and succinic dehydrogenase. The histoenzymic distribution of monoamine oxidase, non-specific esterase, alkaline phosphatase and glucose-6-phosphatase was also recorded. The study revealed moderate to intense activity in glandular areas of gall bladder for majority of enzymes reflecting higher metabolic activity. The enzyme activity was weak to moderate in different tunics of gall bladder and mild to moderate in vascular areas. The differential enzyme activity in different tunics of gall bladder was correlated with metabolic activity of cells.